QUALITATIVE ANALYSIS OF THE MEANING OF EARLY STIMULATION FOR PARENTS OF CHILDREN ONE TO THREE YEARS OLD - Chenet Zuta, Manuel Enrique (2020)
The study sought to identify the meaning given toearly stimulation by parents of children between the agesof one and three at the Early Stimulation Center of theProvincial Municipality of Huancavelica. The researchbelongs to the qualitative approach, descriptive level andinductive-deductive method. The design was descriptivenon-experimental transectional, the sample was nonprobabilistic for convenience and considered 35 parents.The qualitative technique of content analysis was madethrough the unstructured interview and two focus groups.The data was coded into nine categories: early stimulationas a learning method, as a teaching method, as skillsdevelopment, ages, importance, perception of the earlystimulation session, perception of the materials and /or equipment used in the early stimulation room, earlystimulation related to the development of intelligence,transcendence at home. It is concluded that parentsconsider early stimulation sessions important as they arefundamental for the child's cognitive, emotional and socialdevelopment, also establishing that the meanings thataddress technical categories are not accurate with reality,being necessary for parents receive more detailed andaccurate information.